The role of probiotics in adolescents’ obesity - Chen, Xiao-ping; You, Li; Jia, Yong (Frontiers in Cellular and Infection Microbiology, 2025)
The prevalence of adolescent obesity continues to rise globally, posing significant public health challenges by affecting both physical and psychological wellness and increasing the risk of metabolic diseases in adulthood. Probiotics may influence obesity through various mechanisms, including restoring gut microbiota balance, reducing chronic inflammation, modulating lipid metabolism, aiding in weight control, and improving metabolic health. This review aims to explore the mechanisms by which probiotics act as key modulators of obesity and summarize current findings from clinical trials involving probiotics in adolescent obesity. The large-scale, multicenter, long-term follow-up randomized controlled trials are necessary to determine the optimal probiotics strains, dosages, and treatment durations, as well as to assess their long-term efficacy and safety in the future. Through such rigorous studies, probiotics have the potential to become a safe, effective, and accessible adjunct in the comprehensive management of adolescent obesity, offering a more holistic approach to health management for this population.